Perkembangan Kota Awal Islam: Basrah, Kufah, Fustat dan Qairawan - Devi Liasari (Medan Resource Center, 2023)
The expansion of Islamic territories in the past led to the placement of new political and religious elites in conquered areas, resulting in the development of cosmopolitan communities between Arabs and non-Arabs. As part of this expansion, the Islamic government constructed cities in new areas that were originally military defense camps, including Basra and Kufah in Iraq, Fustat in Egypt, and Qairawan in North Africa. This research seeks to explain how these empty lands could transform into thriving Islamic cities. Using the historical method, which includes heuristics, verification, interpretation, and historiography, the researcher found that the military settlements provided a strong foundation for the establishment of Islamic rule in new territories. This was supported by the formation of a military elite group that helped build civilization by making government centers the focal point for Islamic intellectual and literary activity.